The degree to which social studies teachers practice some productive thinking skills in basic education school (Journal of Hama University, 2026)
The research aims to identify the degree of practicing some productive thinking skills by social studies teachers in basic education schools in Tartous city. The researcher used the descriptive approach, and the tool was a questionnaire directed to social studies teachers to know the degree of their practicing some productive thinking skills in their schools. It consisted of (23) paragraphs prepared by the researcher and applied to a sample of (152) male and female teachers drawn using a stratified random method. The research results showed that the degree of practicing some productive thinking skills by social studies teachers was average. There were also statistically significant differences in the degree of practicing some productive thinking skills by social studies teachers according to the academic qualification variable in favor of those holding a diploma in educational qualification and a university degree. As for the educational stage variable, differences were found in favor of first-cycle teachers. While there were no differences between teachers according to the variable of the number of years of experience. In light of the research results, the researcher suggested the need for social studies teachers to pay attention to encouraging learners to criticize ideas, infer information, and employ educational methods that help in critical thinking and creative thinking.The research aims to identify the degree of practicing some productive thinking skills by social studies teachers in basic education schools in Tartous city. The researcher used the descriptive approach, and the tool was a questionnaire directed to social studies teachers to know the degree of their practicing some productive thinking skills in their schools. It consisted of (23) paragraphs prepared by the researcher and applied to a sample of (152) male and female teachers drawn using a stratified random method. The research results showed that the degree of practicing some productive thinking skills by social studies teachers was average. There were also statistically significant differences in the degree of practicing some productive thinking skills by social studies teachers according to the academic qualification variable in favor of those holding a diploma in educational qualification and a university degree. As for the educational stage variable, differences were found in favor of first-cycle teachers. While there were no differences between teachers according to the variable of the number of years of experience. In light of the research results, the researcher suggested the need for social studies teachers to pay attention to encouraging learners to criticize ideas, infer information, and employ educational methods that help in critical thinking and creative thinking.
Keywords: Productive Thinking Skills - Social Studies Teachers.